Islamic Influencers on TikTok: Dakwah Narratives and Digital Authenticity - Ahmad Zuhdi; Nina Anis; Chenda Dara (Yayasan Adra Karima Hubbi, 2025)
Background. The rapid growth of social media platforms has reshaped the way religious content is disseminated, particularly among younger audiences. TikTok, as one of the most popular social media platforms, has emerged as a significant space for Islamic influencers to engage in dakwah (Islamic preaching), reaching millions globally. Purpose. The study aims to investigate how influencers maintain the balance between religious teachings and the entertainment-driven nature of TikTok, and how this balance impacts the perception of authenticity among their followers. Method. A mixed-methods approach, including content analysis, interviews, and surveys, was used to gather data from 10 prominent Islamic influencers and 100 followers. Results. The findings show that influencers who incorporate personal stories, humor, and cultural references into their dakwah are perceived as more authentic, while maintaining audience engagement. However, challenges related to the commercial nature of TikTok and the potential compromise of religious depth were also identified Conclusion. This study concludes that TikTok offers a unique platform for Islamic dakwah, but it requires careful navigation of digital authenticity and content integrity to maintain credibility.